2021
DOI: 10.1186/s12877-021-02606-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of alcohol consumption on cognitive function in seniors: a cohort study in China

Abstract: Background In the context of increasing global aging, the long-term effects of alcohol consumption on cognitive function in older adults were analyzed in order to provide rationalized health recommendations to the elderly population. Methods The study used the Chinese Longitudinal Healthy Longevity Survey (CLHLS) dataset, from which 5354 Chinese seniors aged 65–112 years were selected as the subjects, spanning the years 1998–2018. Data on alcohol, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The association between alcohol consumption and CI may be influenced by dosage. Long-term drinking has been linked to an increased risk of cognitive decline ( 73 ). A dose-response meta-analysis has demonstrated that low intake of alcohol intake (< 11 g/day) is associated with a reduced risk of CI ( 74 ), while individuals who abstain from drinking or consuming high levels of liquor have an elevated risk ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between alcohol consumption and CI may be influenced by dosage. Long-term drinking has been linked to an increased risk of cognitive decline ( 73 ). A dose-response meta-analysis has demonstrated that low intake of alcohol intake (< 11 g/day) is associated with a reduced risk of CI ( 74 ), while individuals who abstain from drinking or consuming high levels of liquor have an elevated risk ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, at higher concentrations, alcohol's effects are the opposite and can increase the risk for developing neurodegenerative diseases. Its consumption can promote dysregulation in the adult brain, and high consumption patterns such as binge drinking (defined as 4 for women, or 5 for men, alcoholic drinks within a 2 h period and reaching clinical intoxication levels) seem to be more associated with cognitive decline than lower alcohol consumption patterns ( Grønkjær et al, 2019 ; Han and Jia, 2021 ; Sabia et al, 2014 ; Zhang et al, 2020 ). This might be further moderated by drinking patterns and preferred alcoholic beverage ( Han and Jia, 2021 ).…”
Section: Adultsmentioning
confidence: 99%
“…Although research involving the effects of alcohol in aging subjects is limited, differential neurobiological effects have been described, even at low doses of alcohol. For example, studies in humans show that older adults perform worse in tests assessing working memory, attention, and cognition as compared to younger adults ( Garcia, Lewis, Boissoneault, & Nixon, 2020 ; L. Han & Jia, 2021 ; Lewis, Boissoneault, Frazier, & Nixon, 2016 ; Price, Lewis, Boissoneault, Frazier, & Nixon, 2018 ). Regarding studies in animal models, the main effects of alcohol that have been evaluated are cognition, ataxia, hypothermia, and sedation.…”
Section: Alcohol Abuse Disorders and Agingmentioning
confidence: 99%